Surgical site infection following incisional negative pressure wound therapy in lower limb amputation closure: A randomized controlled trial - Satya Prakash Meena; Spoorthi D. Shetty; Mayank Badkur; Mahendra Lodha; Mahaveer Singh Rodha; Ramkaran Chaudhary; Naveen Sharma (Journal of Education and Health Promotion)
BACKGROUND: Major amputations are a standard procedure being done for various etiologies of the lower limb. Surgical site infections often complicate the postoperative outcome of patients. Negative pressure wound therapy has evolved to have a preventive role in SSI. According to the best of our knowledge, this is the first study that compared the wound and overall outcomes of incisional application of NPWT against standard dressing in patients undergoing stump closure following major lower limb amputations. The primary goal was to compare the rate of surgical site infections. The secondary objectives were to compare the postoperative hospital stay, reinterventions, readmission, and mortality. MATERIALS AND METHODS: A randomized controlled trial was conducted in a healthcare institute and included 62 patients who underwent closure of major lower limb amputation stumps. After stump closure, patients were randomized into iNPWT and standard groups for the dressing over the suture line. Surgical site infection and other outcomes were assessed. RESULTS: A statistically significant difference was found in the rate of surgical site infection (16% vs 51%, P = 0.003). Also, it appreciated a significant reduction in the number of patients needing reinterventions (26% vs 52%, P = 0.037) and the duration of postoperative hospital stay (5.8 days vs 8.2 days, P = 0.043) in the iNPWT group. CONCLUSION: Incisional application of NPWT following lower limb amputations is an effective tool to reduce surgical site infections, the need of multiple reinterventions, the cost of treatment, and hospital stay. We should use this special dressing as a standard protocol for the high-risk patients undergoing stump closure following major amputations; therefore, it can reduce the morbidity of patients.